Ring-Opening Polymerization of Lactones Catalyzed by Silicon-Based Lewis Acid - Yuushou Nakayama; Keiya Katagi; Ryo Tanaka; Takeshi Shiono (International Journal of Polymer Science)
Many catalysts containing various elements at their active sites have been reported for the ring-opening polymerization (ROP) of cyclic esters. However, to our knowledge, silicon-based catalysts for ROP have never been reported. Here we report the ROP of cyclic esters and cyclic carbonates catalyzed by the derivatives of bis(perchlorocatecholato)silane (Si(catCl)2), which is a neutral silicon-based Lewis acid recently reported by Greb et al. The catalyst systems show high activity for the ROP of seven- and six-membered ring monomers such as ε-caprolactone, δ-valerolactone, and trimethylene carbonate to produce the polymers with molecular weights up to 32 kg/mol. The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and nuclear magnetic resonance analysis of the obtained polymers indicates the predominant formation of cyclic polymers.